Mechanistic Insights in the Success of Fecal Microbiota Transplants for the Treatment of Clostridium difficile Infections - Baktash, Amoe; Terveer, Elisabeth M.; Zwittink, Romy D.; Hornung, Bastian V. H.; Corver, Jeroen; Kuijper, Ed J.; Smits, Wiep Klaas (Frontiers in Microbiology, 2018)
Fecal microbiota transplantation has proven to be an effective treatment for infections with the gram-positive enteropathogen Clostridium difficile. Despite its effectiveness, the exact mechanisms that underly its success are largely unclear. In this Review, we highlight the pleiotropic effectors that are transferred during fecal microbiota transfer and relate this to the C. difficile lifecycle. In doing so, we show that it is likely that multiple factors contribute to the elimination of symptoms of C. difficile infections after fecal microbiota transplantation.